Analysis of Knowledge and Family Support on Coping Strategy of Diabetes Mellitus Patients - Wartana, I Kadek; Gustini, Gustini; V Pelima, Robert; Desy Purnama Sari, Niluh; Heiwer Matongka, Yulian (Rifa'Institute, 2023)
Introduction: Diabetes is a chronic disease in the form of a metabolic disorder characterized by blood sugar levels that exceed normal limits. Diabetes mellitus patients use coping strategy to deal with stressors due to their illness. Good coping strategy are supported by knowledge and family support from people with diabetes mellitus. Objective: to analyze the relationship between knowledge and social support with coping strategy of diabetes mellitus patients. Methods: Quantitative research with a cross sectional study approach. Respondents in this study were 32 diabetes mellitus patients who were taken by accidental sampling at Tinggede Primary Health Center. Data collection used a questionnaire consisting of respondent characteristics, knowledge, family support, and coping strategy. Data were analyzed using the chi square test with a 95% confidence interval. Result and Discussion: The chi-square test results showed that the p value for knowledge was 0.047 (p value < 0.05), and the p value for family support was 0.01 (p value < 0.05). The results of the regression test showed that the significant value for family support (0.001) was smaller than long suffered (0.004) and knowledge (0.031). Conclusion: there is a significant relationship between knowledge and family support with coping strategy in diabetes mellitus patients.